Hydrophobic coatings based on SiO2 - Porębska, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The method of conversion, properties and usage of hydrophobic coatings on the bases of silicon dioxide is presented in the article. These layers are formed by use the silanes which are not react with water. What is more, these layers could provide not only great resistance to the effect of water molecules, but also better resistance to the effect of abrasive action and hardness as well as keeping the top stair of the transparency. Uncomplicated methods such as zol-zel are used to settling these layers. There are methods of putting on the various surfaces, without necessity of usage specific and sophisticated technological solutions. As a transparent and simple to keep in the cleanness surfaces these layers found application in various field such as sport, motorization, building industry, optical system whether in our houses.